Complications following replantation of primary teeth: a case report - Mariana Oliveira Guimarães; Lorena Teixeira Melo Bomfim; Paulo Antônio Martins-Júnior; Fernanda Bartolomeo Freire-Maia; José Carlos Pettorossi Imparato; Patrícia Maria Zarzar (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Introduction: the avulsion of primary teeth is a disturbing and unexpected event. Description: this report describes the clinical case of a three-year-old child who suffered an avulsion and replantation of the primary upper central incisors at the site of the injury. The guardians sought treatment for the child at the Federal University of Minas Gerais after the replantation. Four months later, the child suffered a new trauma and the replanted teeth presented advanced mobility, root resorption and fistula. The clinical conduct was extraction and rehabilitation with a fixed esthetic maintainer. Discussion: the literature describes two treatment options for avulsion of primary incisors: replantation and non-replantation. According to a recent systematic review, the difficulty in obtaining a consensus regarding the best clinical conduct is due, in part, to the scarcity of publications that present not only follow-ups with clinical success, but also with failures. The outcomes of replantation can be influenced by several factors. The time elapsed between replantation and splinting, and the new episode of trauma, negatively influenced the prognosis in the present case, leading to failure. Replantation of primary incisors is not yet evidence-based treatment. Therefore, this option must be chosen with caution and in ideal situations. It requires constant clinical and radiographic monitoring for evaluation of outcomes.